Evaluating Profitability and Livelihood Empowerment and Sustainability in Shadow Entrepreneurship: A Case of Street Vending in Dharan Sub-Metropolitan City of Eastern Nepal - Gajurel, Ram Prasad; Poudel, Tanka Mani; Khatiwada, Aadhar; Sapkota, Bed Prasad (Journal of Vishwa Adarsha College, 2024)
Street vending is emerging as a significant shadow entrepreneurial activity, impacting a substantial portion of the urban population. This study, centered in Dharan City, Eastern Nepal, investigates the profitability of street vending and its impact on empowering and sustaining lives and livelihoods. Through structured interviews with 50 purposively selected street vendors, the research identifies key determinants of profitability, such as education, investment, marital status, livestock ownership, and consumption patterns. Findings suggested that married vendors, those with livestock and residential property, and those prudent in educational spending tend to achieve higher profits. Conversely, individuals with low capital investment, from rural areas, and maintaining moderate consumption may experience adverse effects on profitability. The findings also underscored the crucial role of street vending in individual survival, livelihood empowerment, social inclusion, and sustainability. The findings provide valuable insights for local-level policymakers struggling to harness the complexities of growing urban economies by regulating and managing street vendors' activities across Nepal.